The Life of Imam Abi Zara'a: the Iraqi Kurd Imam and his Scientific Efforts (Islamic Sciences Journal, 2023)
The research came as an answer to many of the questions that came to mind, before uttering and responding to them with the tongue, and to prove the participation of Kurdish Muslims and that they are not less than others in constructing and protecting the structure of Islam, and understanding its teachings and knowledge of it. Therefore they had established and participated in building Islamic thought and its civilization with others, away from the alien ethnic national sense, by showing and raising its banner in scientific forums and its fields, as they raised it in the arenas of jihad and protecting its nucleus, and their scientific councils were full, in addition to their participation in the fields of investigation, authorship, commentary and footnotes, in various types of knowledge, in parallel lines with their worship and teaching in mosques and schools, Along with their involvement in the soldiers' companies and brigades, and their link in the front.
Keywords: Abi Zaraa, his scientific life, a statement of his doctrine, his works, praise.